Harnessing Mechanistic Knowledge on Beneficial Versus Deleterious IFN-I Effects to Design Innovative Immunotherapies Targeting Cytokine Activity to Specific Cell Types - Tomasello, Elena; Pollet, Emeline; Vu Manh, Thien-Phong; Uzé, Gilles; Dalod, Marc (Frontiers in Immunology, 2014)
Type I interferons (IFN-I) were identified over 50 years ago as cytokines critical for host defense against viral infections. IFN-I promote antiviral defense through two main mechanisms. First, IFN-I directly reinforce or induce de novo in potentially all cells the expression of effector molecules of intrinsic antiviral immunity. Second, IFN-I orchestrate innate and adaptive antiviral immunity. However, IFN-I responses can be deleterious for the host in a number of circumstances, including secondary bacterial or fungal infections, several autoimmune diseases, and, paradoxically, certain chronic viral infections. We will review the proposed nature of protective versus deleterious IFN-I responses in selected diseases. Emphasis will be put on the potentially deleterious functions of IFN-I in human immunodeficiency virus type 1 (HIV-1) infection, and on the respective roles of IFN-I and IFN-III in promoting resolution of hepatitis C virus (HCV) infection. We will then discuss how the balance between beneficial versus deleterious IFN-I responses is modulated by several key parameters including i) the subtypes and dose of IFN-I produced, ii) the cell types affected by IFN-I and iii) the source and timing of IFN-I production. Finally we will speculate how integration of this knowledge combined with advanced biochemical manipulation of the activity of the cytokines should allow designing innovative immunotherapeutic treatments in patients. Specifically, we will discuss how induction or blockade of specific IFN-I responses in targeted cell types could promote the beneficial functions of IFN-I and/or dampen their deleterious effects, in a manner adapted to each disease.